(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Stature is one of the basic requisites in Forensic anthropology that can aid in the identification of an individual. It helps to distinguish between multiple individuals who are the same in ancestry, sex, and age, providing a circumstantial or presumptive identification. Human skull is sometimes recovered without other long bones and stature estimation using human cranium can give valuable information about stature of that individual thus helping in its identification. There are very few studies of stature estimation using cranial dimensions in India and hence this current research aims to utilize the different cranial dimensions and to test the accuracy and validity of these measurements in estimating the stature on Indian population. There is significant correlation of stature with these parameters for both males and females in this study, the standard error of estimate in the present study is about 5 to 8 cm. Linear regression analysis was done to estimate stature.